1999
DOI: 10.1074/jbc.274.22.15869
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Molybdenum into the Iron-Molybdenum Cofactor of Nitrogenase

Abstract: The biosynthesis of the iron-molybdenum cofactor (FeMo-co) of dinitrogenase was investigated using 99 Mo to follow the incorporation of Mo into precursors. 99 Mo label accumulates on dinitrogenase only when all known components of the FeMo-co synthesis system, NifH, NifNE, NifB-cofactor, homocitrate, MgATP, and reductant, are present. Furthermore, 99 Mo label accumulates only on the gamma protein, which has been shown to serve as a chaperone/insertase for the maturation of apodinitrogenase when all known co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The hypothesis of a FeMo-co biosynthetic factory has been formulated before (67) to explain the observed distribution of radioactively labeled FeMo-co precursors between the NifH, NifEN, NifX, and NafY proteins during the biosynthesis of FeMo-co in vitro (2, 3,57,58). This hypothesis is also consistent with the recently reported distribution of FeMo-co precursors between NifEN and NifH as analyzed by EXAFS (36,38).…”
Section: The Femo-co Biosynthetic Factory Modelsupporting
confidence: 77%
“…The hypothesis of a FeMo-co biosynthetic factory has been formulated before (67) to explain the observed distribution of radioactively labeled FeMo-co precursors between the NifH, NifEN, NifX, and NafY proteins during the biosynthesis of FeMo-co in vitro (2, 3,57,58). This hypothesis is also consistent with the recently reported distribution of FeMo-co precursors between NifEN and NifH as analyzed by EXAFS (36,38).…”
Section: The Femo-co Biosynthetic Factory Modelsupporting
confidence: 77%
“…This interaction has not been observed in previous anoxic native gel electrophoresis (33,34) nor in our native gel electrophoresis experiments (data not shown). It is possible that the conditions used to assay the interaction of NifB-co and NafY by fluorescence are milder to the complex than those of native gel electrophoresis.…”
Section: Figmentioning
confidence: 43%
“…50-l samples were subsequently electrophoresed for 20 h in an anoxic native gel that was finally stained with Coomassie Brilliant Blue. NifB-co or labeled molybdenum from a FeMo-co precursor have been found associated to NafY only if all the components necessary for FeMo-co biosynthesis are present in the assay mixture (33,34). These results have been taken as evidence of FeMo-co being synthesized and accumulated on NafY.…”
Section: Figmentioning
confidence: 75%
“…Prior to this study, 99 Mo-labeling of NifNE has not been observed. Previous studies (17,18) have involved the use of crude cell extracts, and two possible reasons for not observing the incorporation of 99 Mo into NifNE could be the interference from other proteins present in the cell extracts, or that the synthesis of FeMo-co is allowed to proceed beyond NifNE. The purified in vitro FeMo-co synthesis reaction is a well-defined system and, being devoid of other extraneous components present in crude enzyme preparations, has facilitated the identification of hitherto undetected incorporation of a FeMo-co precursor into NifNE.…”
Section: Incorporation Of 99 Mo Into Components Of the In Vitro Femo-mentioning
confidence: 99%